Effect of supplementing coconut or krabok oil, rich in medium-chain fatty acids on ruminal fermentation, protozoa and archaeal population of bulls. (18th November 2013) - Panyakaew, P.; Boon, N.; Goel, G.; Yuangklang, C.; Schonewille, J. Th.; Hendriks, W. H.; Fievez, V.
Abstract : Medium-chain fatty acids (MCFA), for example, capric acid (C10:0), myristic (C14:0) and lauric (C12:0) acid, have been suggested to decrease rumen archaeal abundance and protozoal numbers. This study aimed to compare the effect of MCFA, either supplied through krabok (KO) or coconut (CO) oil, on rumen fermentation, protozoal counts and archaeal abundance, as well as their diversity and functional organization. KO contains similar amounts of C12:0 as CO (420 and 458 g/kg FA, respectively), but has a higher proportion of C14:0 (464 v. 205 g/kg FA, respectively). Treatments contained 35 g supplemental fat per kg DM: a control diet with tallow (T); a diet with supplemental CO; and a diet with supplemental KO. A 4th treatment consisted of a diet with similar amounts of MCFA (i.e. C10:0+C12:0+C14:0) from CO and KO. To ensure isolipidic diets, extra tallow was supplied in the latter treatment (KO+T). Eight fistulated bulls (two bulls per treatment), fed a total mixed ration predominantly based on cassava chips, rice straw, tomato pomace, rice bran and soybean meal (1.5% of BW), were used. Both KO and CO increased the rumen volatile fatty acids, in particular propionate and decreased acetate proportions. Protozoal numbers were reduced through the supplementation of an MCFA source (CO, KO and KO+T), with the strongest reduction by KO. Quantitative real-time polymerase chain reaction assays based on archaeal primers showed a decrease in abundance of Archaea when supplementing with KO and KO+T compared with T and CO. The denaturing gradient gel electrophoresis profiles of the rumen archaeal population did not result in a grouping of treatments. Richness indices were calculated from the number of DGGE bands, whereas community organization was assessed from the Pareto–Lorenz eveness curves on the basis of DGGE band intensities. KO supplementation (KO and KO+T treatments) increased richness and evenness within the archaeal community. Further research including methane measurements and productive animals should elucidate whether KO could be used as a dietary methane mitigation strategy.